Project-Based Learning Effect on Improving Students’ Creative Thinking in Static Fluid Learning - Ahmad Fikri Alfarizki; Ai Nurlaela; Devi Solehat (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
The low creative thinking ability of students in understanding physics concepts, especially in static fluid material, is one of the problems that needs attention in the learning process. Therefore, this study aims to determine how the Project Based Learning (PjBL) learning model that uses a scientific approach affects students' ability to think creatively about static fluid material. The research method used is a quasi-experimental design with a Nonequivalent Control Group Design. The research subjects consisted of two eleventh grade high school students, namely the experimental class using the scientific PjBL model and the control class using the Inquiry Learning model, each consisting of 30 students. The research instrument was a descriptive test consisting of eight questions developed based on Torrance's creative thinking indicators, including fluency, flexibility, originality, and elaboration. The data obtained were analyzed through normality tests, homogeneity, and N-gain calculations. The results showed that the average N-gain of the experimental class's creative thinking ability was 0.41 (medium category), higher than the control class which only reached 0.29 (low category). Specifically, significant improvements were seen in the fluency and flexibility indicators, while the originality and elaboration indicators also increased although relatively lower. Thus, it can be concluded that the application of the scientific PjBL model is more effective in improving students' creative thinking abilities compared to the Inquiry Learning model in static fluid learning. These findings are expected to contribute to the development of physics learning strategies oriented towards strengthening creativity, independence, and active involvement of students in the knowledge construction process.